A Morphological and Anatomical Study of Tamarix aphylla (Tamaricaceae) in Iraq Central Region - Al-Msary, Anwar Naji; Al-Ani , Mazin Nawaf (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The Tamarix aphylla is a wild perennial shrub with erect stems that are long and glabrous. They have leaves that are simple, alternate, sheathed, and the apex of the blade is acuminate. And a scaly clawed bract and the the inflorescences were simple, spike-like. The pistil consists of ovary pyramidal, 3 styles, and 3 stigmas. The androecium consists of five stamens that are antisepalous. The perianth was distinct with five sepals and five petals. The fruits were capsule-shaped, pyramidal, and smooth. The seed has an apical pappus of unicellular hygroscopic hairs; endosperm is absent. The anatomical study of the leaves contained a uniseriate epidermis consisting of one layer of elongated cells covered by a layer of papillary cuticle. The upper epidermis cells are larger than the lower epidermis cells, and the stomata were anomocytic. The mesophyll consists of one layer of palisade cells and several layers of irregular, spongy cells. The stem epidermis is uniseriate, which is a single row of circular to ovate cells covered by a layer of papillary cuticle. The cortex is composed of two tissues, collenchyma and parenchyma; lamellate collenchyma tissue consists of 1-2 layers of cells; and parenchyma tissue consists of several layers of cells. The vascular bundle was ovate. The pith tissue consisted of circular parenchyma cells that were thin-walled and occupied the central part of the stem.